ROCK1 regulates sepsis-induced acute kidney injury via TLR2-mediated endoplasmic reticulum stress/pyroptosis axis. (October 2021) - Wang, Qian-Lu; Xing, Wei; Yu, Can; Gao, Min; Deng, Long-Tian
Highlights: ROCK1 is highly expressed in sepsis-induced AKI. ROCK1 regulates NLRP3-mediated pyroptosis. ROCK1 regulates pyroptosis via TLR2-mediated ERS. ROCK1 regulates sepsis-induced AKI via TLR2-mediated ERS/pyroptosis axis. Abstract: Background: It has been reported that ROCK1 participates in the progression of multiple diseases, including septic intestinal barrier, cardiac dysfunction and acute lung injury. However, its regulatory role and specific mechanism in sepsis-induced acute kidney injury (AKI) remain unclear. Methods: Cecal ligation puncture (CLP) was conducted to establish sepsis mouse model, and in vitro model was achieved by lipopolysaccharide (LPS) stimulation. Genes expression was evaluated by qRT-PCR, western blot or ELISA was conducted to assess the levels of proteins. Hoechst staining was performed to evaluate cell pyroptosis. LDH activity assay was detected to assess cytotoxicity. Immunohistochemistry was conducted to detect Ly-6G expression and neutrophils distribution in kidney tissues of mice. H&E and TUNEL staining were carried to evaluate kidney injury of mice. Results: Our findings illuminated that ROCK1 was highly expressed in sepsis-induced AKI, and ROCK1 knockdown inhibited NLRP3-mediated cell pyroptosis in LPS-induced HK-2 cells. Moreover, ROCK1 modulated HK-2 cell pyroptosis by regulating endoplasmic reticulum stress (ERS). TLR2 inhibitor could suppress ERS mediated cell pyroptosis under LPS treatment. Further, TLR2 activator partially reversed the effects of ROCK1 inhibition on ERS mediated pyroptosis in LPS-treated HK-2 cells and CLP mice. Conclusion: In conclusion, ROCK1 may regulate sepsis-induced AKI via TLR2-mediated ERS/pyroptosis axis. Our data demonstrated the role and underlying mechanism of ROCK1 in septic AKI, providing theoretical basis for sepsis-induced AKI treatment.